Pengaruh Budaya Belajar Terhadap Motivasi Belajar Yang Dimediasi Dengan Persepsi Kualitas ( Studi Kasus Pada Mahasiswa di Universitas Cipasung Tasikmalaya) - Sindy Kania Suryani; Sri Sudiarti (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the influence of learning culture on learning motivation with perceived university quality as a mediating variable. The research method uses a quantitative approach with data collected through questionnaires to students of Cipasung University Tasikmalaya, then analyzed using the SEM-PLS method. The results show that learning culture has a positive and significant effect on learning motivation and perceived university quality. Perceived quality also has a positive and significant effect on learning motivation. In addition, perceived quality is proven to act as a mediating variable that strengthens the influence of learning culture on learning motivation. This study contributes in explaining the importance of learning culture and perceived quality in increasing student learning motivation, and can be a basis for universities in improving the quality of learning